2016
DOI: 10.1007/s00401-016-1548-y
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral monocytes are functionally altered and invade the CNS in ALS patients

Abstract: Amyotrophic lateral sclerosis (ALS) is a devastating progressive neurodegenerative disease affecting primarily the upper and lower motor neurons. A common feature of all ALS cases is a well-characterized neuroinflammatory reaction within the central nervous system (CNS). However, much less is known about the role of the peripheral immune system and its interplay with CNS resident immune cells in motor neuron degeneration. Here, we characterized peripheral monocytes in both temporal and spatial dimensions of AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
141
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(156 citation statements)
references
References 67 publications
11
141
4
Order By: Relevance
“…The major populations increased in ALS and aging were from monocyte and macrophage lineages. These changes are consistent with other studies that have found robust activation of these cells as part of the immune response during ALS disease progression and aging (Butovsky et al, 2012; Chiu et al, 2009; Galbavy et al, 2017; Kullberg, Aldskogius, & Ulfhake, 2001; Zondler et al, 2016). …”
Section: Resultssupporting
confidence: 91%
“…The major populations increased in ALS and aging were from monocyte and macrophage lineages. These changes are consistent with other studies that have found robust activation of these cells as part of the immune response during ALS disease progression and aging (Butovsky et al, 2012; Chiu et al, 2009; Galbavy et al, 2017; Kullberg, Aldskogius, & Ulfhake, 2001; Zondler et al, 2016). …”
Section: Resultssupporting
confidence: 91%
“…25,26 In mouse models, it has been suggested that peripheral monocytes/macrophages infiltrated spinal cords during the course of disease using Ly6C and CD169 as markers for monocytederived macrophages. 18 Our results indicate that monocytes of patients with ALS may participate in the inflammatory response associated with disease progression; more inflammation-related DEGs are observed in rapid phase than slow phase. Thus, manipulating monocytes at an early stage in disease may directly promote the development of therapy for patients with ALS.…”
Section: + /Cd16mentioning
confidence: 83%
“…18,19 All of these data suggest that ALS monocytes are involved in proinflammatory responses and may promote active inflammation. The monocytes isolated by negative selection in our study included both CD16 + and CD16 − monocytes.…”
Section: + /Cd16mentioning
confidence: 95%
“…DNA was extracted from whole EDTA-containing venous blood samples as described 21. Analysis of the C9orf72 repeat length was performed by fragment length analysis and repeat-primed PCR (RP-PCR) using previously published primers 22 23.…”
Section: Methodsmentioning
confidence: 99%